Frequency of cell treatment with cold microwave argon plasma is important for the final outcome. (4th July 2016) - Sysolyatina, E; Vasiliev, M; Kurnaeva, M; Kornienko, I; Petrov, O; Fortov, V; Gintsburg, A; Petersen, E; Ermolaeva, S
Abstract: The purpose of this work was to establish the influence of a regime of cold microwave argon plasma treatments on the physiological characteristics of human fibroblasts and keratinocytes. We used three regimes of plasma application: a single treatment, double treatment with a 48 h interval, and daily treatments for 3 d. Cell proliferation after plasma application was quantified in real time, and immunohistochemistry was used to establish the viability of the cells and determine changes in their physiology. It was established that the frequency of cell treatments is important for the outcome. In the samples treated with single plasma application and double plasma applications with a 48 h interval, a 42.6% and 32.0% increase was observed in the number of cells, respectively. In addition, there were no signs of deoxyribonucleic acid breaks immediately after plasma application. In contrast, plasma application increased the accumulation of cells in the active phases of the cell cycle. The activation of proliferation correlated with a decrease in the level of β -galactosidase, a senescence marker. This could be due to cell renovation after plasma application. Daily treatment decreased cell proliferation up to 29.1% in comparison with the control after 3 d.